Decision-making in Humanitarian Operations - Strategy, Behavior and Dynamics (2018)
This book brings together research in humanitarian operations, behavioral operations and dynamic simulation. Part I outlines the main characteristics and strategic challenges of humanitarian organizations in preparedness, knowledge management, climate change and issues related to refugees and social inclusion. Part II gives an introduction to behavioral operations and experiments in single- and multi-agent settings, followed by discussions on quantal theory, framing effect and possible applications in the humanitarian sector. Part III introduces system dynamics and agent-based modeling and discusses how these techniques can be used to study dynamics and decision-making in humanitarian operations, with a focus on disaster management problems, collaborative strategies in humanitarian logistics and supply chains with heterogeneous decision makers. This book is unique in providing a holistic view of the decision-making process and challenges in the humanitarian sector.